Conservadorismo à brasileira : sociedade e elites políticas na contemporaneidade - Quadros, Marcos Paulo dos Reis (2015)
This thesis analyzes the nature of the conservatism in contemporary Brazil, emphasizing the values rooted in the popular mind, the recent movements of civil society and the political elites behavior in National Congress. In order to present the meanings of different "conservatisms" in space and time, the research begins with a theoretical mapping of the basic principles of conservative political philosophy, from Edmund Burke to the American neoconservatism. Then, using surveys published by opinion research institutes, it outlines the features of "the Brazilian way of conservatism" and of the traditional values held by significant segments of the population. However, the thesis suggests that the electoral potential of conservatism has not been fully exploited by the major Brazilian political parties, which, in the wake of the "leftist consensus" created during the military regime, remain reproducing the phenomena of "ashamed right", especially in party programs and in the political platforms presented in presidential elections. Nevertheless, this "representative vacuum" would have been felt by sectors of civil society and of the National Congress. Thus, intellectuals, opinion makers and recent social movements have been encouraging a "culture war" in order to win public opinion and implement conservative values also in the political sphere. At he same time, the thesis argues that groups such as the "evangelical bench" and the "bullet bench" have overcome the feeling of "ashamed right" and started to introduce overtitly conservative agendas in parliament, gradually minimizing the "representative vacuum" produced by the political parties.